1994
DOI: 10.1161/01.cir.89.5.2204
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor antagonist TCV-116 induces regression of hypertensive left ventricular hypertrophy in vivo and inhibits the intracellular signaling pathway of stretch-mediated cardiomyocyte hypertrophy in vitro.

Abstract: BACKGROUND Previous studies have demonstrated that angiotensin II (Ang II) acts as a growth-promoting factor directly on cardiac myocytes and that angiotensin-converting enzyme inhibitor induces regression of hypertrophied hearts both in experimental animals and in humans. These results suggest that the renin-angiotensin system (RAS) is involved in the formation of left ventricular hypertrophy (LVH). To elucidate the role of RAS in the progression of cardiac hypertrophy, we evaluated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
12

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(109 citation statements)
references
References 40 publications
5
92
0
12
Order By: Relevance
“…These results indicated that candesartan was superior to hydralazine as far as renal protection was concerned. 15 It has been reported that losartan 16,17 and candesartan cilexetil [18][19][20][21][22] also protected the development of cardiac hypertrophy in spontaneously hypertensive rats (SHR), but hydralazine did not, 19,21,22 although it reduced BP, supporting the assumption that AT 1 receptor antagonists have protective action against cardiac hypertrophy independent of BP-lowering action. In DOCA/salt hypertensive rats losartan also inhibited cardiac hypertrophy despite not having a significant anti-hypertensive action.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that candesartan was superior to hydralazine as far as renal protection was concerned. 15 It has been reported that losartan 16,17 and candesartan cilexetil [18][19][20][21][22] also protected the development of cardiac hypertrophy in spontaneously hypertensive rats (SHR), but hydralazine did not, 19,21,22 although it reduced BP, supporting the assumption that AT 1 receptor antagonists have protective action against cardiac hypertrophy independent of BP-lowering action. In DOCA/salt hypertensive rats losartan also inhibited cardiac hypertrophy despite not having a significant anti-hypertensive action.…”
Section: Discussionmentioning
confidence: 99%
“…injection of nifedipine (Bayer Yakuhin, Ltd., Tokyo, Japan) (10 mg/kg/day) three times a day through the right jugular vein; 3) continuous infusion of nifedipine (10 mg/kg/day, 0.5 µl/h) by a subcutaneously implanted osmotic minipump (Alzet ® , model 2002; Muromachi Kikai Co., Ltd., Tokyo, Japan). All treatments were started from the age of 12 weeks, when cardiac hypertrophy had already developed (17), and continued to 24 weeks (Fig. 1).…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…1). Systolic blood pressure (BP) and heart rate (HR) were measured before treatment and every week after administration of vehicle or nifedipine using the tail-cuff plethysmography method in conscious rats (17). After 4, 8 and 12 weeks of treatment, 6 rats of each group were subjected to the following analyses.…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…13 We further investigated the relation between hypertensive cardiac hypertrophy and the cardiac reninangiotensin system. 14 In an in vivo study, spontaneously hypertensive rats (SHR) were assigned to the treatment with a nonpeptide Ang II type 1 receptor antagonist of candesartan or a vasodilating agent of hydralazine. Blood pressure was measured by a tail cuff method, and the wall thickness of the left ventricle was serially monitored using M-mode echocardiography.…”
Section: Haemodynamic Overload and The Cardiac Renin-angiotensin Systemmentioning
confidence: 99%